Zircons, dikes and gold mineralization at Jundee-Nimary: post ca 2.66 Ga Archean lode gold in The Yandal Belt, Western Australia. - Baggott, M.; Vielreicher, N.; Groves, David.; McNaughton, Neal; Gebre-Mariam, M. (Society of Economic Geologists Inc, 2005)
In recent years, there has been considerable controversy concerning the timing of lode gold mineralization in the Yilgarn craton. The majority of published robust direct and indirect geochronological constraints indicate that orogenic gold deposits formed broadly in the period 2655 to 2625 Ma, with most between 2645 and 2630 Ma. Recent studies, however, have suggested that gold mineralization in the Yandal belt may be significantly older, with the implication that gold deposits could be diachronous across the craton over approximately 40 m.y. Critical to this assertion is that essentially unmineralized, broadly north-northeast– to northeast-trending, granodiorite porphyry dikes at the Jundee-Nimary gold deposits are postore intrusions and that the age of one of the dikes, the Moore porphyry, is 2669 ± 7 Ma based on U-Pb SHRIMP geochronology. Reassessment of field relationships indicates that the Moore porphyry and other granodiorite dikes control the position of anomalously oriented ore shoots where the dikes bend from their common north-northeast to northeast orientation into a more east- northeast trend. In the Nim 6 deposit, one such granodiorite dike hosts gold-related veins and alteration and anomalous gold grades. Contrary to previous interpretations, the Moore porphyry is a preore dike that was relatively unaffected by deformation and related ore fluid because it was oriented broadly parallel to σ1 at the time of gold mineralization.Reexamination of zircons from the Moore porphyry indicates that they have volumetrically dominant cores, interpreted to be xenocrysts, with narrow magmatic rims. The previous age of 2669 ± 7 Ma includes at least some core analyses. By specifically targeting magmatic zircon rims, a more robust magmatic age of 2657 ± 6 Ma is obtained. Thus, not only is the Moore porphyry a pre- rather than postore dike, but its mean age is about 10 m.y. younger than that previously recorded. The new data require that the absolute maximum age of mineralization at Jundee-Nimary is 2663 Ma, whereas previous results suggested a minimum age of 2662 Ma. In combination with other indirect constraints on the age of gold mineralization in the Yandal belt, there is no evidence to suggest that the Jundee-Nimary gold deposits did not form in the same broad 2655 to 2625 Ma range as most other Yilgarn gold deposits. This study illustrates that dikes that are unfavorably oriented for failure in the regional stress field may appear to be postore because they are largely unmineralized, but detailed examination at all scales is required for unequivocal interpretation. Similarly, zircons may give unrealistically old ages if their internal morphologies and growth histories are not carefully considered prior to analysis.